COST STRUCTURE ANALYSIS IN DETERMINING SELLING PRICES USING THE COST PLUS PRICING METHOD IN THE DEPULA ADZRA FOOD BUSINESS IN GORONTALO CITY - Syahla Badjeber; Hartati Tuli; Ikhlas Ul Aqmal (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to determine the Cost Structure in Determining Selling Prices using the Cost Plus Pricing method in the Depula Adzra food business in Gorontalo City. The type of research used in this study is a Quantitative method with a Descriptive approach. The data used are primary data in the form of interviews, Observations and Documentation with the owner of the Depula Adzra business. The results of the study show that the calculation of selling prices using the cost plus pricing method shows a difference with the selling price set by the business. The selling price of goat kabuli rice according to Depula Adzra is IDR 1,000,000, while based on the cost plus pricing method it is obtained at IDR 1,269,055. Conversely, on the beef kabuli rice menu, the selling price according to Depula Adzra is IDR 800,000, while the calculation result of the cost plus pricing method is IDR 1,037,673. This difference shows that the determination of selling prices in the business is not entirely based on systematic cost calculations.